2022
DOI: 10.3390/jcm11195620
|View full text |Cite
|
Sign up to set email alerts
|

Head-Of-Bed Elevation (HOBE) for Improving Positional Obstructive Sleep Apnea (POSA): An Experimental Study

Abstract: Purpose: Evaluate the effectiveness of the head-of-bed elevation position (HOBE) with a 30° elevation of the head and trunk, in improving obstruction of the upper airways in obstructive sleep apnea (OSA) patients. A prospective trial simultaneously performing drug-induced sleep endoscopy (DISE) and polysomnography (PSG) tests was performed. Methods: Forty-five patients were included in the prospective study protocol. All patients enrolled in the study and underwent the following evaluations: (1) a drug-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In our study, 51.8% of experts agreed with performing a velopharyngeal surgery; however, in this case, 27.7% disagreed, and 21.4% were neutral. According to the expert consensus statement on pediatric persistent obstructive sleep apnea postadenotonsillectomy management, expansion pharyngoplasty proves to be a secure and effective remedy for pediatric patients facing persistent OSA associated with lateral wall collapse identified during DISE [1,33].…”
Section: Patient's Indications According To Pediatric Dise Outcomesmentioning
confidence: 99%
“…In our study, 51.8% of experts agreed with performing a velopharyngeal surgery; however, in this case, 27.7% disagreed, and 21.4% were neutral. According to the expert consensus statement on pediatric persistent obstructive sleep apnea postadenotonsillectomy management, expansion pharyngoplasty proves to be a secure and effective remedy for pediatric patients facing persistent OSA associated with lateral wall collapse identified during DISE [1,33].…”
Section: Patient's Indications According To Pediatric Dise Outcomesmentioning
confidence: 99%
“…A special mattress with a hole for the face was proposed in order to allow to breathe in a prone face down position. Last but not least, our group is collecting an increasing amount of evidence about the use of 30° Fowler’s position in managing positional OSA in a more comprehensive way 21 ;…”
Section: Rescue Optionsmentioning
confidence: 99%
“…They found that the intervention significantly reduced the AHI and abolished OSA in over 50% of cases [51]. Collapsibility was even more favorable in upright vs. lateral position [52] and at 30° head-elevation [53 ▪ ]. These improvements are likely facilitated by better anatomical features in the upright position [54], by a reduced gravitational vector effect through mobile upper airway structures [55], and by a supine-to-reclined position reduction in overnight rostral fluid shift [56], especially in patients with comorbid heart failure [57].…”
Section: Supine Obstructive Sleep Apnea Pathogenesismentioning
confidence: 99%